2011
DOI: 10.1007/s10585-011-9396-6
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK signaling mediates plasticity of scirrhous gastric carcinoma motility

Abstract: The small guanosine triphosphatase (GTPase) Rho and its downstream effector Rho-associated kinase (ROCK) is one of a key mediator involved in controlling focal adhesions and the dynamics of actin stress fibers. The molecular mechanisms for the function of Rho/ROCK pathway leading to the progression in scirrhous gastric carcinoma cells have not been defined. The activation of RhoA in several gastric carcinoma cells was examined. The role of RhoA/ROCK pathway in the metastatic processes of gastric carcinoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Conversely, Rho-kinase signaling can activate the Rac GAP ARH-GAP22 to suppress mesenchymal movement by inactivating Rac (25). The increased invasion of gastric cancer cells following treatment with ROCK1/2 inhibitors can be blocked with a Rac1 inhibitor (64), further demonstrating significant crosstalk between Rac1 and ROCK1/2 signaling. Overall, our results demonstrate the differential effects of Snail and Slug in pancreatic cancer and identify the interplay between Rho signaling and ␤1-integrin that functions to regulate scattering and migration of pancreatic cancer cells by Snail and Slug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Rho-kinase signaling can activate the Rac GAP ARH-GAP22 to suppress mesenchymal movement by inactivating Rac (25). The increased invasion of gastric cancer cells following treatment with ROCK1/2 inhibitors can be blocked with a Rac1 inhibitor (64), further demonstrating significant crosstalk between Rac1 and ROCK1/2 signaling. Overall, our results demonstrate the differential effects of Snail and Slug in pancreatic cancer and identify the interplay between Rho signaling and ␤1-integrin that functions to regulate scattering and migration of pancreatic cancer cells by Snail and Slug.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that inhibiting Rho signaling using a dominant negative Rho mutant or ROCK1/2 inhibitors enhances migration of squamous cell cancer cells on collagen I (63). ROCK1/2 inhibitors also enhance invasion of gastric cancer cells through Matrigel (64). Rac1 and ROCK1/2 signaling have also been demonstrated to have an antagonistic effect on each other's cellular behavior (65).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also shown that Y-27632 increased the invasiveness of human glioma U87 and U251 cells [110] and also enhanced the invasion of human gastric carcinoma OCUM-2MD3 cells [111]. Time-lapse microscopy showed conversion of OCUM-2MD3 cells from a round to a more elongated morphology in the presence of Y-27632, and the expression of membrane-type 1 matrix metalloproteinase (MT1-MMP) was elevated, suggesting that inhibition of the RhoA/ROCK pathway undergoes AMT.…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 98%
“…The Rho family GTPase RhoA has been implicated in the regulation of cell contraction and retraction forces that are required for cell migration and invasion (20). In the current study, the activity of RhoA in glioblastoma cells in response to resveratrol was examined using a pull-down assay.…”
Section: Resveratrol Inhibits Activity and Expression Of Mmp-2 In Glimentioning
confidence: 99%